Alcohol use and smoking in burn patients at the Helsinki Burn Center. Issue 1 (February 2018) - Palmu, Raimo; Partonen, Timo; Suominen, Kirsi; Vuola, Jyrki; Isometsä, Erkki
Highlights: A prospective follow-up study; alcohol use and smoking among acute burn patients. A cohort of consecutive acute hospitalized burn patients (n = 107). More than half of burn patients were under the influence of alcohol and one-fourth had smoking-related activity at the time of the burn. In both groups lifetime mental disorders, especially alcohol use disorder before burn, were very common. Abstract: Objective: We investigated alcohol use and smoking at time of burn and their relationships with severity of burn and presence of mental disorders. Methods: Consecutive acute burn patients (N = 107) admitted to the Helsinki Burn Center were assessed with the structured clinical interview for mental disorders (SCID) at baseline and after 6 months. Information regarding being under the influence of alcohol and having smoking-related activity at burn as well as about hazardous drinking (Alcohol Use Disorders Identification Test) and heavy smoking before the burn was recorded. Results: Around half (52%) of the acute burn patients were under the influence of alcohol and 19% had been both drinking and smoking at the time of the burn. Patients under the influence at the time of burn had significantly higher prevalence of lifetime mental disorders compared to those patients who were not under the influence of alcohol (73.2% vs. 45.1%, p = 0.003), especially alcohol dependence (55.4% vs. 13.7%, p < 0.001) and anxiety disorders (28.6% vs. 9.8%, p = 0.015). Patients who had both alcohol use and smoking at burn had even more often at least one mental disorder (95.0% vs. 51.7%, p < 0.001), in specific alcohol dependence (90.0% vs. 23.0%, p < 0.001), or psychotic disorder (25.0% vs. 6.9%, p = 0.016). The main characteristics of the burns themselves did not differ significantly between these groups. Conclusion: Half of the burn patients were under the influence of alcohol at the time of the burn in this study. In almost all patients where alcohol and smoking contributed to the burn a diagnosable alcohol use disorder was present. Interventions for those with alcohol use disorders and the associated risk behaviors are important for the prevention of burns.